Revitalizing Islamic Education: Professionalism of State Islamic Religious College Lecturers in Welcoming the Industrial Era 4.0 - Imran, Imran; Mardhiah, Ainal (Jurnal Ilmiah Peuradeun, 2023)
This study focused on three aspects: 1) the professionalism of lecturers in the Faculty of Tarbiyah and Teacher Training (FTK) at the State Islamic Religious College (PTKIN) in Aceh in welcoming the industrial revolution 4.0 era; 2) the skills of FTK lecturers at PTKIN in Aceh in using technology for teaching; and 3) strategies to develop the professional competence of FTK lecturers in welcoming the industrial revolution 4.0 era. This research applied a qualitative method with fifty informants from FTK-PTKIN in Aceh. The informants were determined purposefully: two deans, one head of the Department of Teacher Training and Education, six deputy deans, and forty-nine lecturers. Data collection was done through interviews, observations, and documentation, and the data were analyzed through three steps: data reduction, data presentation, and conclusion drawing. This study revealed that FTK-PTKIN lecturers in Aceh have high professional competence and good skills in using technology for teaching to welcome the Industrial Revolution 4.0 era. The common media used in teaching are Google Classroom, Google Meet, Zoom, and WhatsApp. Moreover, the professional competence of FTK lecturers is developed through the following strategies: doctoral education, technology training, and scholarship provision.